Macrolide resistance in pneumococci—is it relevant?. Issue 1 (December 2016) - Cheng, Allen; Jenney, Adam
Abstract Macrolide antibiotics are widely used for a range of indications, including pneumonia. Both high-level and low-level resistance to macrolides is increasing in pneumococci globally. Macrolide resistance in pneumococci is of limited clinical relevance where ß-lactams remain the mainstay of treatment, such as for moderate/severe pneumonia; however, data suggest that macrolides may not be able to be relied on as monotherapy for serious pneumococcal infections.